1997
DOI: 10.1084/jem.186.7.1137
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with DNA Encoding the Immunodominant LACK Parasite Antigen Confers Protective Immunity to Mice Infected with Leishmania major

Abstract: To determine whether DNA immunization could elicit protective immunity to Leishmania major in susceptible BALB/c mice, cDNA for the cloned Leishmania antigen LACK was inserted into a euykaryotic expression vector downstream to the cytomegalovirus promoter. Susceptible BALB/c mice were then vaccinated subcutaneously with LACK DNA and challenged with L. major promastigotes. We compared the protective efficacy of LACK DNA vaccination with that of recombinant LACK protein in the presence or absence of recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
260
6
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(277 citation statements)
references
References 53 publications
9
260
6
2
Order By: Relevance
“…Upon adoptive transfer into naive recipients, LC loaded with a mixture of the recombinant Leishmania Ag LACK, KMP-11, gp63, and PSA were shown to mediate significant protection against a challenge with L. major parasites. The significance of LC as the vaccine carrier is emphasized by the previous observation that gp63, LACK, and KMP-11 are unable to induce protective responses when administered as proteins without adjuvant (23,28,31). Most importantly, we identified LeIF as a single leishmanial Ag that, upon loading into LC, protected mice from uncontrolled parasite infection.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Upon adoptive transfer into naive recipients, LC loaded with a mixture of the recombinant Leishmania Ag LACK, KMP-11, gp63, and PSA were shown to mediate significant protection against a challenge with L. major parasites. The significance of LC as the vaccine carrier is emphasized by the previous observation that gp63, LACK, and KMP-11 are unable to induce protective responses when administered as proteins without adjuvant (23,28,31). Most importantly, we identified LeIF as a single leishmanial Ag that, upon loading into LC, protected mice from uncontrolled parasite infection.…”
Section: Discussionmentioning
confidence: 87%
“…For this purpose, several prominent Leishmania Ag were chosen that have already been shown to be strongly immunogenic. The Leishmania homolog of receptor for activated C kinase (LACK) is a highly conserved intracellular protein that has been shown to play an important role in the immunopathogenesis of experimental L. major infections (21,22), and vaccination with DNA encoding LACK induces protection against a challenge with parasites (23). Leishmania homolog of eukaryotic ribosomal elongation and initiation factor 4a (LeIF) is a Leishmania protein that elicits IL-12 production and a Th1 response of human PBMCs (24).…”
mentioning
confidence: 99%
“…APCs can directly uptake the DNA vaccine and present the expressed antigen, or the DNA vaccine can also be expressed by somatic cells, and the released antigen is then picked up by APCs (53). Major APCs involved in DNA vaccines appear to be the dendritic cells (20), and several studies have demonstrated that introduction of plasmid encoding GM-CSF results in the accumulation of dendritic cells in vivo (21,31). Dendritic cells stimulated with GM-CSF are also known to differentiate and mature into increasingly effective APCs (42).…”
Section: Discussionmentioning
confidence: 99%
“…The protective immunity detected was mostly mediated by specific CD4 Th1 cells, although protective immunity was also partly dependent on CD8 T lymphocytes (Gurunathan et al 1997). A further evaluation of the role of CD8 T cells found that they may function as helpers for the development of effector CD4 T cells.…”
Section: Toxoplasma Gondii and Leishmania Spmentioning
confidence: 99%